The Relationship Between Burning Factors and Mediterranean Climatic Conditions in the Croatian Coastal Part - Roman Rosavec; Damir Barčić; Toni Rožman; Damir Ugarković (Fire)
Climate conditions have long been recognised as an important factor influencing the start and spread of forest fires in Mediterranean areas. This is partly due to the long dry periods that characterise these regions. Mixed forest ecosystems are more stable than monocultures. This study was conducted at two sites, the city of Makarska (the southern coast of the Croatian Mediterranean) and the island of Rab (the northern island of the Croatian Mediterranean). The main variables examined, flammability, combustion and the moisture content of potential forest fuel, best define the start and spread of fires. The aim of the study was to examine the influence of climate factors on these variables using the example of mock privet (Phillyrea latifolia L.). The results showed that moisture content of fuel was a key variable in direct correlation with the influence of climate factors. Though the Mediterranean region is burdened by fires and they will continue to occur in the future due to changing conditions, the study results can contribute to reducing burned areas in fires for the purpose of preserving Mediterranean ecosystems.